A Phase I Trial of TB-403 in Relapsed Medulloblastoma, Neuroblastoma, Ewing Sarcoma, and Alveolar Rhabdomyosarcoma - Saulnier-Sholler, Giselle; Duda, Dan G.; Bergendahl, Genevieve; Ebb, David; Snuderl, Matija; Laetsch, Theodore W.; Michlitsch, Jennifer; Hanson, Derek; Isakoff, Michael S.; Bielamowicz, Kevin; Kraveka, Jacqueline M.; Ferguson, William; et al. (Clinical cancer research, 2022)
Placental growth factor (PlGF) and its receptor neuropilin 1 are elevated in malignant embryonal tumors and mediate tumor progression by promoting cell proliferation, survival, and metastasis. TB-403 is a blocking monoclonal antibody against PlGF that inhibits tumor growth and increases survival in orthotopic medulloblastoma models. We conducted a phase I, open-label, multicenter, dose-escalation study of TB-403 in pediatric subjects with relapsed or refractory cancers. The study involved four dose levels (20 mg/kg, 50 mg/kg, 100 mg/kg, 175 mg/kg) using a 3 + 3 dose-escalation scheme. Subjects received two doses of TB-403 (days 1 and 15) per cycle. After cycle 1, temozolomide or etoposide could be added. The primary objective was to determine the maximum tolerated dose (MTD) of TB-403 monotherapy during a dose-limiting toxicity assessment period. The secondary and exploratory objectives included efficacy, drug pharmacokinetics, and detection of pharmacodynamic biomarkers. Fifteen subjects were treated in four dose levels. All subjects received two doses of TB-403 in cycle 1. Five serious treatment-emergent adverse events were reported in 3 subjects, but MTD was not reached. While no complete nor partial responses were observed, 7 of 11 relapsed subjects with medulloblastoma experienced stable disease, which persisted for more than 100 days in 4 of 7 subjects. TB-403 was safe and well tolerated at all dose levels. No MTD was reached. The results look encouraging and therefore warrant further evaluation of efficacy in pediatric subjects with medulloblastoma.